Management and follow up of extra–adrenal phaeochromocytoma - Barski, Dimitri (Polish Urological Association, 2014)
INTRODUCTION: The prevalence of phaeochromocytoma (PCC) in patients with hypertension is 0.1–0.6% and about 10% of PCCs are detected in extra–adrenal tissue. The diagnosis and therapy of this rare disease detected as a retroperitoneal tumor mass can be difficult for clinicians. MATERIAL AND METHODS: A PubMed database was searched for the peer–reviewed articles, the listed articles until Dec 2012 were included. Following key words were used: “extra–adrenal phaeochromocytoma”, “paraganglioma”, “diagnosis”, “therapy”, “surgery”, “genetic analysis”, and “SDH mutation”. RESULTS: Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) are first choice imaging tools for PCC (sensitivity 90–100%). For the validation of the diagnosis or follow up, the functional imaging 123I–metaiodobenzylguanidine (MIBG) or Fluorine–18–L–dihydroxyphenylalanine (18F–DOPA) positron emission tomography (excellent specificity and sensitivity of 90–100% in detection of small tumors >1–2 cm) are used. Laparoscopic surgery with complete resection is a safe and a first choice approach. The conversion (about 5%) to direct open operation was needed for large lesions (>8 cm) with the suspicion of malignancy. Currently, there are no histological criteria for distinguishing benign and malignant tumors. The genetic testing (Sanger DNA sequencing) for hereditary syndromes (von Hippel–Lindau, neurofibromatosis, etc.) is used for prediction of malignancy and recurrence. All patients should get individual and risk–adapted genetic analysis and consultation, including family members. The rate of malignancy in ePCC is about 30% (PCC about 5–10%). In patients with proven SDHB germline mutations, higher malignancy rate, multiple PCCs and recurrences are likely. A stringent lifelong clinical follow–up is recommended in these cases. Patients with syndromic hereditary forms should be screened for other often associated neoplasms. CONCLUSIONS: New imaging tools and genetic analysis are crucial to improve the diagnosis and prognosis of phaeochromocytoma.